Rancang Bangun Aplikasi Perhitungan Harga Pokok Produksi Pada CV. LIntas Nusa - Loropatty, Theresiya; Supriyanto, Antok; Mastan, Ignatius Adrian (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Abstract:  CV. Lintas Nusa is a company engaged in the field of offset printing and digital printing. This company is a printing where a minimum order 4 reams of paper, except that large can be in the order in small amounts. CV. Lintas Nusa hereinafter called the company's production process if there is an order.In the CV. Lintas Nusa, customer first perform mold goods orders in the sales department. After receiving orders from customers, the sales department will calculate the cost of production of each item of customer orders. The calculation of the cost of production is calculated from the cost of raw materials and direct labor costs, and 30 percent advantage of the company to obtain the selling price of each item. After completing the calculation of cost of production and sales price, the sales department will confirm the total price to the customer, if the customer agrees to the price, the sales department will store data on the customer order receipt transaction order printed materials. Upon receipt of a customer order and calculate the cost of production, the purchasing department will undertake the making purchases orders, purchasing department made a list of all the raw material requirements for each customer order. Making Purchases order to help facilitate the purchasing department in the purchase of raw materials, so that all the necessary raw material requirements listed. Part of purchase of raw materials purchases. Problems faced by the company is, the current CV. Lintas Nusa in the calculation of the cost of production, not all costs included in the calculation of the cost of production. The costs included in cost of production is only the cost of materials and direct labor costs, while the overhead costs are not included in the calculation of the cost of production. As a result, the cost of production resulting smaller and not appropriate. This affects the price offered by the company to customers and also affect earnings, the company can not know and do not generate profits that actually. In addition, the problems faced by the company is, as long as the company does not make a report the cost of production so that the company can not know the cost of production per period.